ANALISIS KESULITAN SOAL MATERI ARITMETIKA SOSIAL PADA SISWA SMP - Octaviyani Muslimatul Fitri; Martin Bernard (IKIP Siliwangi, 2021)
This study aims to determine the difficulty analysis of social arithmetic material for junior high school students. During the Covid-19 pandemic, researchers wanted to know and analyze students' difficulties in solving problems in social arithmetic material. The data collection technique in this study, using the WhatsApp Group, the researcher gave 6 description test questions through the WhatsApp Group in the form of a PDF file, then the students collected the results of the answers to the WhatsApp Group or via personal messages. Furthermore, students' answers were analyzed to determine the extent of the difficulties that occurred in students according to predetermined indicators. The data analysis technique was carried out by counting the number of student errors in solving each item, then the errors were analyzed for difficulties. Research subjects in junior high school students amounted to 20 students. The results of the analysis obtained by the researcher, there are still many students who have difficulty working on the questions, it can be seen in the indicators of understanding, determining profits and the percentage of students' answer taxes is 30%. Some students also do not understand the meaning of the questions asked. From the answers that have been done, there are also many students who answer freely and have nothing to do with the material that has been conveyed.